Briquets: solid combustible from heavy oil and biomass - Requena, A.; Spech, M.; Pérez, M. (Rev. Téc. Fac. Ing. Univ. Zulia)
Amixture of 8° API oil (45 parts). Cartb PIDe biomass (50.5 parts) and limestone (4.5 parts) produced a semi-solid that was compacted at 1000 psi after thermal treatment at 400°C, producing a high calorific power combustible briquette. Biomass granulometry acts on the density and compressive strength in the thermally treated briquettes. The addition of petroleum coke and limes tone to the formulation increased calorific power and sulfur retention in the ashes.